Organizational, Technical and Behavioral Factors Associated with Malaria Routine Data Reporting among Health Workers in Selected Health Facilities in Trans-Nzoia County, Kenya - Lagat, Nicholas; Oyore, J; Korir, J. (Journal of Health, Medicine and Nursing, 2022)
Purpose: Malaria remains to be among the primary causes of sickness, infirmity and cases of deaths and has continued to negatively affect health and socio-economic progress in the country. Rapid reporting of malaria cases could avert prospective epidemics which would lead to a high proportion of sickness and deaths. The study, therefore, sought to assess the determinants of malaria routine data reporting among health workers in selected health facilities in Trans-Nzoia County. Methodology: A descriptive cross-sectional study was conducted to evaluate the organizational, technical, and behavioral aspects that influence the reporting of malaria routine data among health workers. The sample size was 123 health facilities that were selected randomly based on their strata. Research tools that were utilized were structured questionnaires, focused group discussion, and key informant interview guide. Chi-square (Ï‡2) was used to test the hypothesis with a p â‰¤ 0.05 being considered significant. Findings: The findings on socio-demographic characteristics indicated that majority of the research participants were females 76(62.6%), had college education 85(69.1%) and 81 (65.9%) had worked in the health facility for 5 to 10 years. Most 76(61.8%) of the health facilities were Level 3 (Health Centres). There was significant relationship between level of health facility and malaria routine data reporting at (Ï‡2 =9.999, df=3, p-value = 0.019). Other organizational factors that had significant association with malaria routine data reporting (p< 0.001) include inadequate budget, low staffing, poor ICT infrastructure and complex data management procedures. In terms of technical aspects, limited training on technologies had significant relationship with malaria routine data reporting (p< 0.001). Regarding behavioral aspects, identified factors include lack of incentives and inadequate resources. Unique contribution to theory, practice and policy: The outcomes of the study provide proof for support, tactical organization, and collaboration in the health sector in Trans-Nzoia County as well as to the other developmental agencies working in the field of malaria control. The study recommends that the county government of Trans-Nzoia should provide adequate funds and ICT infrastructure to boost malaria routine data reporting. The county department of health with support from the national government through Division of National Malaria Program (DNMP )should consistently conduct in-service training, support supervision and data quality audits.